ADAPTIVE STRATEGIC MANAGEMENT–OBE MODEL FOR CURRICULUM INNOVATION BASED ON GRADUATE LEARNING OUTCOMES AT ISLAMIC HIGHER EDUCATION INSTITUTIONS - Irnawati, Wati; Wulandari, Fitri; Nurjanah, Sinta; Purwanti, Neng Yayu (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Addressing the dual challenge of modernizing competencies while preserving Islamic identity, this study develops the Adaptive Strategic Management–Outcome-Based Education (MSA-OBE) model. Purpose: This research addresses the critical skills mismatch in Private Islamic Religious Higher Education Institutions (PTKIS), specifically STAI Al-Azhary Cianjur, in the VUCA era. Method: Using a qualitative approach with a conceptual case study design, data were synthesized from systematic literature reviews, institutional strategic documents, and external environmental mapping. Result: The resulting MSA-OBE model operates through four continuous phases: strategic environmental scanning based on Islamic values, adaptive curriculum strategy formulation through modularization, flexible project-based implementation, and data-driven evaluation. Conclusion: This model transforms static curricula into adaptive ecosystems, producing graduates with hybrid competencies that balance spirituality, intellectuality, and professional skills. Implication: The findings provide a strategic framework for PTKIS to maintain institutional relevance and competitiveness in the modern industrial landscape.